1997
DOI: 10.1038/ng0697-161
|View full text |Cite
|
Sign up to set email alerts
|

The BCL-6 proto-oncogene controls germinal-centre formation and Th2-type inflammation

Abstract: Structural alterations of the promoter region of the BCL-6 proto-oncogene represent the most frequent genetic alteration associated with non-Hodgkin lymphoma, a malignancy often deriving from germinal-centre B cells. The BCL-6 gene encodes a zinc-finger transcriptional repressor normally expressed in both B cells and CD4+ T cells within germinal centres, but its precise function is unknown. We show that mice deficient in BCL-6 displayed normal B-cell, T-cell and lymphoid-organ development but have a selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
614
3
5

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 740 publications
(636 citation statements)
references
References 48 publications
14
614
3
5
Order By: Relevance
“…Under the study conditions we describe, CD138 and VS38 were more effective and specific in detecting plasmacytic differentiation in tissue microarrays as well as in individually tested cases of LPL and MZL. Our findings of the immunoreactivity of CD138 and VS38 in LPL and MZL with and without plasmacytic differentiation are entirely in agreement with previous studies for these markers (24,25,27,28,(45)(46)(47)(48). Although careful morphologic correlation of consecutive sections in cases immunoreactive for all three markers revealed similar patterns of distribution of stained cells, MUM1 consistently stained a larger number of lesional cells than did CD138 or VS38.…”
Section: Figuresupporting
confidence: 93%
“…Under the study conditions we describe, CD138 and VS38 were more effective and specific in detecting plasmacytic differentiation in tissue microarrays as well as in individually tested cases of LPL and MZL. Our findings of the immunoreactivity of CD138 and VS38 in LPL and MZL with and without plasmacytic differentiation are entirely in agreement with previous studies for these markers (24,25,27,28,(45)(46)(47)(48). Although careful morphologic correlation of consecutive sections in cases immunoreactive for all three markers revealed similar patterns of distribution of stained cells, MUM1 consistently stained a larger number of lesional cells than did CD138 or VS38.…”
Section: Figuresupporting
confidence: 93%
“…Like in frog (Hilton et al, 2007;Sakano et al, 2010), BCoR mutations randomize LR asymmetry in human embryos (Ng et al, 2004;Hilton et al, 2007), but this does not occur in mouse (Ye et al, 1997;Yoshida et al, 1999). The loss of brain asymmetry observed in mouse mutants with ciliary dyskinesia (Kawakami et al, 2008) is not observed in human patients (Kennedy et al, 1999;Tanaka et al, 1999;McManus et al, 2004;Afzelius and Stenram, 2006).…”
Section: The Mouse As a Model For Mammalian Asymmetrymentioning
confidence: 94%
“…5'RACE analysis of the BCL6 transcripts was performed using the 5'RACE kit (GIBCO/BRL) following manufacturer's recommendations. The primers used for cDNA ampli®cation were as previously described (Ye et al, 1997), except that the reverse primer 567 (AGGGTT-GATCTCAGGATC) at exon 4 was also used for the ®nal ampli®cation. The ®nal PCR product was subcloned into PGEM-T (Promega) and sequenced.…”
Section: Mutation Analysis and Expression Of Bcl6 Alleles By Rt ± Pcrmentioning
confidence: 99%
“…The BCL6 gene encodes a POZ/Zinc ®nger transcription factor which functions as a sequence speci®c transcription repressor Chang et al, 1996;Seyfert 1996;Baron et al, 1997). The primary function of BCL6 appears to be regulation of germinal center (GC) development and T-cell directed immune response (Dent et al, 1997;Ye et al, 1997). Activating BCL6 rearrangements have been shown to result from chromosomal translocations with IG or other loci that alter BCL6 expression by promoter substitution, or from point mutations in the 5' regulatory region (Migliazza et al, 1995;Ye et al, 1995;Chen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%